METHODOLOGY FOR THE EXTRACTION OF HOMOLOGOUS POINTS FROM A DEM/DSM TO EVALUATE THE RELATIVE POSITIONAL ACCURACY - Santos, Afonso de Paula dos (2020)
This work presents a new methodology for extracting 3D homologous points from a DEM/DSM for relative evaluation of positional accuracies, from terrain features such as ridgelines and hydrography. Firstly, it extracts 3D intersection points between the linear features and then it performs a selection of these homologous points. A discussion regarding the spatial resolution effect of the DEM/DSM on the proposed methodology is carried out. As case study, the planimetric and altimetric positional accuracies evaluation of SRTM (X-band) and Aster GDEM (version 2) DSMs was conducted using, as reference, a DSM obtained via photogrammetry. The SRTM and Aster GDEM (version 2) DSMs showed similar classifications, that is, Class A for the altimetry and Class B for the planimetry at the 1:100,000 scale, according to the Brazilian technical standard of positional accuracy.